2015
DOI: 10.1007/s10457-015-9849-z
|View full text |Cite
|
Sign up to set email alerts
|

Bamboo based agroforestry systems in Kerala, India: performance of turmeric (Curcuma longa L.) in the subcanopy of differentially spaced seven year-old bamboo stand

Abstract: Bamboo-based agroforestry is a promising option for sustainable land management in India. Optimal management of bamboo-based mixed species production systems, however, requires an understanding of bamboo spacing, root activity and distribution of bamboo roots, and the soil nutrient capital of the site. We examined the performance of turmeric as an understorey crop in 7-year old bamboo (Dendrocalamus strictus (Roxb.) Nees) stands of varying spacing treatments (4 9 4, 6 9 6, 8 9 8, 10 9 10 and 12 9 12 m) at Kera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
(31 reference statements)
5
21
0
1
Order By: Relevance
“…Gao et al (2013) observed the PAR at 0.5 m and 1.5 m distance to the tree row was reduced by 17.9% and 10.4% in apple-soybean intercropping treatment, respectively, and reduced by 17.8% and 5.4% in apple-peanut intercropping treatment. Similar results were reported for gliricidia/maize (Makumba et al 2007), walnut/maize (Jose et al 2000), and bamboo/turmeric (Kittur et al 2016) studies in temperate agroforestry systems. Our results showed that the detected PAR and TPAR values of intercropped wheat were significantly lower than monoculture wheat.…”
Section: Photosynthetically Active Radiation and Photosynthetic Ratesupporting
confidence: 86%
See 2 more Smart Citations
“…Gao et al (2013) observed the PAR at 0.5 m and 1.5 m distance to the tree row was reduced by 17.9% and 10.4% in apple-soybean intercropping treatment, respectively, and reduced by 17.8% and 5.4% in apple-peanut intercropping treatment. Similar results were reported for gliricidia/maize (Makumba et al 2007), walnut/maize (Jose et al 2000), and bamboo/turmeric (Kittur et al 2016) studies in temperate agroforestry systems. Our results showed that the detected PAR and TPAR values of intercropped wheat were significantly lower than monoculture wheat.…”
Section: Photosynthetically Active Radiation and Photosynthetic Ratesupporting
confidence: 86%
“…Lack of light is a major constraint that has affected stability of the structure and function of agricultural ecosystems. Kittur et al (2016) found that low understory photosynthetically active radiation (PAR) is the dominant factor reducing growth of turmeric in dense, compared to widely spaced, bamboo stands. In apple-based intercropping systems, the total aboveground biomass and yield of peanut and soybean had highly linear correlations with PAR (Gao et al 2013).…”
Section: Qiao Institute Of Medicinal Plant Development Chinesementioning
confidence: 99%
See 1 more Smart Citation
“…Piouceau et al (2014) and Yourmila and Bhardwaj (2017) reported that higher competition for nutrients and water among the bamboo plants results into decrease in the survival rate of bamboo plants at higher densities (Piouceau et al, 2014;Yourmila and Bhardwaj, 2017). Increase in number of clumps in higher plantation density results into lack of growth space making competition for light, space and nutrients which reduces growth of new rhizome and culms (Kigomo and Kamiri, 1985) consequential less biomass productivity, confirms an inverse association as higher the plantation densities inferior the biomass yield (Kittur et al, 2016). Soil and agro-climatic conditions were meagre in the present bamboo captive plantation and farmers' field trials.…”
Section: Assumptions and Secondary Data For Calculationssupporting
confidence: 59%
“…Agroforestry systems are land-use systems and technologies where woody perennials are deliberately used on the same land management units as agricultural crops and/or animals [9]. Because bamboo forests are characterized by their short rotation and strong regeneration ability, they can typically be used to establish agroforestry systems as a potential strategy for providing food and nutritional security and for contributing to the economic development of developing countries in the tropics [10]. The use of an agroforestry pattern consisting of moso bamboo and chicken farming has been reported in China [11,12].…”
Section: Introductionmentioning
confidence: 99%